PENGEMBANGAN BUKU CERITA BERGAMBAR UNTUK MENINGKATKAN KETERAMPILAN BERBICARA PESERTA DIDIK KELAS II SEKOLAH DASAR - Risky Erillia; Aisah; Elfi Lailan Syamita Lubis; Nurul Hasanah; Lisa Amelia (Jurnal Sintaksis, 2026)
This research aims to produce a product in the form of a picture story book to improve the speaking skills of class II students. The development model used by ADDIE consists of five stages, namely analysis, design, development, implementation and evaluation. The research was carried out at SD Negeri 050656 Stabat. The research subjects were 20 class II students consisting of 9 female students and 11 male students. The research object is a picture story book. Data collection was carried out through observation, interviews and questionnaires. Data analysis techniques were used to determine the feasibility and effectiveness of picture story books. Based on the research results, it is known that the assessment from material experts showed a percentage of 89.60% in the very appropriate category, validation results from media experts obtained a percentage of 92.75% in the very appropriate category, the results of students' speaking skills during the pretest were 2.23 and increased by 11.62 in the posttest. Based on these results, it was concluded that picture story books could improve the speaking skills of class II students.